Implementation of ERP Systems in Organizational Settings: Enhancing Operational Efficiency and Productivity - Tuli, Ferdouse Ara; Kaluvakuri, Swathi (Asian Business Review, 2022)
Implementing an Enterprise Resource Planning system (ERP) in organizations is a strategic move to enhance efficiency and productivity. This article explores the transformative impact of ERP deployment on businesses. It discusses how ERP systems streamline processes, centralize data, and facilitate informed decision-making. ERPs eliminate redundancy and improve communication by integrating various functions like finance, HR, and supply chain management. The resulting optimization of resource allocation and reduced manual effort leads to increased productivity. Furthermore, ERP systems enable real-time tracking of key performance indicators, fostering proactive responses to market changes. In summary, ERP deployment empowers organizations to achieve heightened operational efficiency and productivity.